Testosterone deficiency, insulin-resistant obesity and cognitive function - Hiranya Pintana (2018)
© Springer Science+Business Media New York 2015. Testosterone is an androgenic steroid hormone, which plays an important role in the regulation of male reproduction and behaviors, as well as in themaintenance of insulin sensitivity. Several studies showed that testosterone exerted beneficial effects in brain function, including preventing neuronal cell death, balancing brain oxidative stress and antioxidant activity, improving synaptic plasticity and involving cognitive formation. Although previous studies showed that testosterone deficiency is positively correlated with cognitive impairment and insulin-resistant obesity, several studies demonstrated contradictory findings. Thus, this review comprehensively summarizes the current evidence from in vitro, in vivo and clinical studies of the relationship between testosterone deficiency and insulin-resistant obesity as well as the correlation between either insulin-resistant obesity or testosterone deficiency and cognitive impairment. Controversial reports and the mechanistic insights regarding the roles of testosterone in insulin-resistant obesity and cognitive function are also presented and discussed.